ANALYSIS OF CRISIS STRATEGIES IN THE CONDITIONS OF MODERN HYBRID WAR - О. Shvydanenko; G. Duginets; O. Tkachenko; A. Kotenok; T. Busarieva (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The totality of modern geopolitical challenges and threats in the new information reality can be characterized as hybrid warfare, which includes a wide range of actions aimed at destruction of all spheres of social life of the rival state. Hybrid wars are now becoming the main instrument of geopolitical confrontation, which actualizes the search for counteraction to such threats. The widespread use of asymmetric crisis management has become an integral part of the practice of diplomacy, the basis for the effective implementation of the national security strategy of any sovereign state. The relevance of the article is due to the fact that hybrid wars today have become an integral part of new geopolitical realities. Asymmetric strategies, together with preventive diplomacy, are extremely relevant instruments of world politics. However, the theory and practice of an asymmetric approach in international relations, despite its relevance, has been developed rather fragmentarily, especially in matters of classification of asymmetric strategies. The main aim of the article is the analysis the role of strategies in the conditions of the modern hybrid war and to figure out the role of knowledge component in the formation of the world competitive leaders. The methodological basis of the article is the methods and forms of scientific knowledge adopted in domestic science, such as system approaches, comparative and synthesis methods, methods of abstract logical evaluation, methods of detailing, groupings and generalizations, experts’ evaluations. The results: the reasons of the hybrid war were revealed, the specific features of crisis strategies were presented, the influence of the knowledge component on the competitiveness of the countries was proved, disruptive technologies on the competitiveness of the national economies were proved, the specific features of the disruptive technologies were presented, the effective asymmetric strategies were underlined.